PENGEMBANGAN BUKU SAKU BERBASIS ETNOBOTANI SUKU MELAYU PADA SUB MATERI ZAT ADITIF KELAS VIII SMP - Tania, Rahmayana Dwi; Sunandar, Ari; Rahayu, Hanum Mukti (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
From the results of interviews with teachers at the IT Baitul Qur'an junior high school, information was obtained that in carrying out learning, teachers used textbooks and worksheets to convey the sub-material of additives. However, these teaching materials have several shortcomings, such as material that is difficult to understand, explanations that are incomplete, and do not display information or examples on the material being explained. This research aims to produce a pocket book media based on the ethnobotany of the Malay tribe of West Kalimantan on the sub-material of additives for class VIII junior high school. The research method used is Research and Development (R&D), with the Alessi and Trolip development model. This research stage has three stages, namely planning, design and development. The results of the research show that the pocket book media based on the ethnobotany of the West Kalimantan Malay tribe that was developed obtained a feasibility score on the media aspect of 92.50% (very valid), the material aspect of 91.67% (very valid), and the linguistic aspect of 90.48 % (very valid). Meanwhile, the results of students' responses to the pocket book based on ethnobotany of the Malay tribe of West Kalimantan obtained a score of 90.14% with very strong criteria. Therefore, it can be concluded that the ethnobotany-based pocket book media that was developed is very suitable for use and received a positive response from students.